English English - Jose Freitas, Caetano (Jurnal Teknik Sipil dan Arsitektur, 2025)
Reinforced concrete (RC) buildings with Special Moment Resisting Frames (SMRF) are widely used in seismic regions due to their superior ductility and energy dissipation capabilities. However, their actual performance under strong ground motions still requires detailed investigation, especially in regions with limited seismic design experience. This study assesses the seismic performance of a four-story SMRF RC building located in Delta-4, Dili, Timor Leste, using nonlinear time history analysis (NLTHA). The structural model was developed in SAP2000 v19 following the provisions of SNI 1726:2019 for seismic design and SNI 2847:2019 for concrete detailing, given their applicability in the absence of national standards. Seven ground motion records were selected and scaled to match the site-specific response spectrum. Key parameters such as story drift ratios, base shear, and plastic hinge development were analyzed. Results show that the building satisfies the Immediate Occupancy (IO) and Life Safety (LS) performance objectives under design-level seismic events. Plastic hinges formed primarily in beams rather than columns, validating a strong-column weak-beam mechanism. Drift ratios remained within acceptable limits, ensuring minimal structural and non-structural damage. The study confirms that properly detailed SMRF RC buildings can perform satisfactorily under earthquake loads, even in regions with emerging seismic design practice. Moreover, it highlights the effectiveness of NLTHA as a tool to support performance-based design in Timor-Leste and recommends further studies for taller structures and varied structural systems in similar contexts.